Sources of increased instability in Indian and U.S. cereal production - Hazell, Peter B. R. (Wiley, 1984)
Recent growth in Indian and U.S. cereal production has been accompanied by a more than proportional increase in the standard deviation of production. This study applies variance decomposition procedures to state data on crop production to analyze the sources of this increased instability. It is found that production has become significantly more covariate between states and crops, largely because of increased yield variability and a loss in offsetting patterns of variation between crop yields in different states. These changes may be associated with more variable prices, with higher‐yielding technologies, and with a narrowing of the genetic base.